Method for laser shock peening of eutectic high-entropy alloys

CN122979608APending Publication Date: 2026-10-27JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610771443.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

现有技术中缺乏针对共晶高熵合金体系的参数适配与系统控制方法,在多脉冲作用条件下强化效果呈现不稳定或非线性变化,难以获得稳定且可重复的强化结果

Benefits of technology

本发明中,所提出的共晶高熵合金的激光冲击强化方法,通过预先构建目标共晶高熵合金的目标激光强化参数与目标激光强化效果的关系,并基于目标激光强化效果以及目标激光强化参数与目标激光强化效果的关系,得到目标激光强化参数的设定值;然后,根据目标激光强化参数的值对目标共晶高熵合金进行激光冲击强化,实现了CoCrFeNiZr0.5共晶高熵合金表层硬度与耐磨性能的协同提升,解决了现有技术中参数适配性差、强化效果不稳定的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979608A_ABST
    Figure CN122979608A_ABST
Patent Text Reader

Abstract

The application discloses a laser shock peening method for eutectic high-entropy alloy, and comprises the following steps: establishing the relationship between the target laser peening parameter of the target eutectic high-entropy alloy and the target laser peening effect; obtaining the target laser peening effect of the target eutectic high-entropy alloy; obtaining the setting value of the target laser peening parameter according to the target laser peening effect and the relationship between the target laser peening parameter and the target laser peening effect; and performing laser shock peening on the target eutectic high-entropy alloy according to the value of the target laser peening parameter. The application realizes the synergistic improvement of the surface hardness and wear resistance of the eutectic high-entropy alloy, and solves the problems of poor parameter adaptability and unstable strengthening effect in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of laser shock technology, and in particular to a laser shock strengthening method for eutectic high-entropy alloys. Background Technology

[0002] Eutectic high-entropy alloys are a class of novel metallic materials composed of multiple main elements forming a stable eutectic microstructure. Among them, the CoCrFeNiZr0.5 alloy is a typical eutectic high-entropy alloy system, usually prepared by vacuum suspension melting to form a eutectic microstructure composed of two phases. This type of material has certain advantages in terms of strength and toughness matching, thus showing potential application prospects in high-temperature structural components and wear-resistant parts. To further improve the surface properties of the material, existing technologies typically employ surface modification methods such as heat treatment, shot peening, roll forming, and coating deposition.

[0003] Laser shock processing (LSP) is a non-contact surface strengthening technique that uses short-pulse high-power lasers to generate plasma shock waves on the material surface, thereby introducing residual compressive stress and dislocation strengthening structures into the material surface. This technique typically achieves the shock strengthening effect by covering the material surface with an absorption layer and a transparent constraint layer, and by controlling the laser shock energy, spot size, and pulse parameters. Existing technology has applied this method to titanium alloys, high-temperature alloys, and some structural steels to improve fatigue life and wear resistance.

[0004] Laser shock peening, a high-energy-density surface modification method, utilizes an absorption layer and a transparent constraint layer on the material surface, coupled with a short-pulse high-power laser output system, to perform shock strengthening treatment on the material surface without mechanical contact. However, existing laser shock peening processes are mainly designed for traditional single-phase or simple microstructure materials. For high-entropy alloys with multiphase eutectic structures, the laser shock energy, the number of laser shocks, the uniformity of the laser spot, and the control method of the absorption and constraint layers significantly affect the shock effect. Current technologies lack parameter adaptation and system control methods specifically for eutectic high-entropy alloy systems, resulting in unstable or nonlinear strengthening effects under multi-pulse conditions, making it difficult to obtain stable and repeatable strengthening results. Summary of the Invention

[0005] To address the technical problems existing in the background art, this invention proposes a laser shock strengthening method for eutectic high-entropy alloys.

[0006] This invention proposes a laser shock peening method for eutectic high-entropy alloys, comprising: Establish the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy; To obtain the target laser strengthening effect of the target eutectic high-entropy alloy; Based on the target laser enhancement effect and the relationship between the target laser enhancement parameters and the target laser enhancement effect, the set values ​​of the target laser enhancement parameters are obtained; Laser shock strengthening of the target eutectic high-entropy alloy is performed based on the values ​​of the target laser strengthening parameters.

[0007] Preferably, the target eutectic high-entropy alloy is a CoCrFeNiZr0.5 eutectic high-entropy alloy.

[0008] Preferably, the process parameters for laser shock strengthening of the target eutectic high-entropy alloy include: laser shock energy, number of laser shocks, overlap rate, spot uniformity, and absorption layer and constraint layer; wherein, the target eutectic high-entropy alloy is located below the absorption layer, and the absorption layer is located below the constraint layer.

[0009] Preferably, the target enhancement parameters include laser shock energy and the number of laser shocks.

[0010] Preferably, the target laser strengthening effect includes hardness and coefficient of friction.

[0011] Preferably, the process of establishing the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy includes: Determine the target strengthening parameters for laser shock strengthening of the target eutectic high-entropy alloy; set the adjustment range of each target strengthening parameter; Based on the enhancement parameters of each target and their control range, an orthogonal experimental scheme was designed. Based on each experimental scheme in the orthogonal experimental scheme, laser shock strengthening was carried out on the target eutectic high-entropy alloy; Hardness and friction wear tests were performed on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various experimental schemes to obtain the target laser strengthening effect of each experimental scheme. Based on various experimental schemes and the target laser strengthening effect, the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy is established.

[0012] Preferably, before performing hardness and friction / wear tests on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various test schemes to obtain the target laser-strengthening effect of each test scheme, the method further includes: Optical and scanning morphology observations, phase diagrams, KAM diagrams, and XRD analyses were performed on the target eutectic high-entropy alloys before and after each experimental scheme.

[0013] Preferably, each test scheme is repeated multiple times, and the average value of the target laser enhancement effect is taken as the final target laser enhancement effect.

[0014] Preferably, in the execution of each test scheme for the target eutectic high-entropy alloy, a laser shock path is designed first; S1. Load the workpiece made of the target eutectic high-entropy alloy into the preset station; S2. Apply the absorbent layer to the workpiece; S3. Open the water flow switch of the constraint layer to form a water layer as a constraint layer; S4. Based on the laser impact path and the process parameters in this test plan, laser impact is applied to the workpiece; S5. After each impact, determine whether the preset number of laser impacts has been reached; If yes, proceed to S6; otherwise, proceed to S2. S6. Remove the workpiece and the absorption layer to obtain the workpiece that completes the test plan. In this invention, the proposed laser shock peening method for eutectic high-entropy alloys pre-constructs the relationship between target laser peening parameters and target laser peening effects for the target eutectic high-entropy alloy. Based on the target laser peening effect and the relationship between the target laser peening parameters and the target laser peening effect, the set values ​​of the target laser peening parameters are obtained. Then, laser shock peening is performed on the target eutectic high-entropy alloy according to the values ​​of the target laser peening parameters, achieving a synergistic improvement in the surface hardness and wear resistance of CoCrFeNiZr0.5 eutectic high-entropy alloy, and solving the problems of poor parameter adaptability and unstable peening effects in the prior art. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the laser shock strengthening method for eutectic high-entropy alloys in one embodiment of the present invention;

[0016] Figure 2 The images show the XRD patterns of the eutectic high-entropy alloy before and after laser shock strengthening in one embodiment of the present invention; where (a) represents 8J, (b) represents 10J, (c) represents 12J, (d) represents 1 laser shock, (e) represents 2 laser shocks, and (f) represents 3 laser shocks.

[0017] Figure 3 The optical morphology of the eutectic high-entropy alloy before and after laser shock peening is shown in one embodiment of the present invention; wherein, (a) represents the phase diagram before laser shock peening, (b) represents 8J-1, (c) represents 8J-2, (d) represents 8J-3, (e) represents 10J-1, (f) represents 10J-2, (g) represents 10J-3, (h) represents 12J-1, (i) represents 12J-2, and (j) represents 12J-3.

[0018] Figure 4The image shows the scanning morphology of a eutectic high-entropy alloy before and after laser shock peening in one embodiment of the present invention; wherein, (a) represents the phase diagram before laser shock peening, (b) represents 8J-1, (c) represents 8J-2, (d) represents 8J-3, (e) represents 10J-1, (f) represents 10J-2, (g) represents 10J-3, (h) represents 12J-1, (i) represents 12J-2, and (j) represents 12J-3.

[0019] Figure 5 The hardness of the eutectic high-entropy alloy after laser shock strengthening in one embodiment of the present invention is shown in (a), where (b) represents 8J, (c) represents 10J, and (c) represents 12J.

[0020] Figure 6 The friction coefficient of the eutectic high-entropy alloy after laser shock strengthening in one embodiment of the present invention is given; wherein, (a) represents 8J, (b) represents 10J, (c) represents 12J, (d) represents 1 laser shock, (e) represents 2 laser shocks, and (f) represents 3 laser shocks.

[0021] Figure 7 This is a phase diagram of a eutectic high-entropy alloy before and after laser shock peening in one embodiment of the present invention; wherein, (a) represents the phase diagram before laser shock peening, (b) represents 8J-1, (c) represents 8J-2, (d) represents 8J-3, (e) represents 10J-1, (f) represents 10J-2, (g) represents 10J-3, (h) represents 12J-1, (i) represents 12J-2, and (j) represents 12J-3.

[0022] Figure 8 The KAM diagrams of the eutectic high-entropy alloy before and after laser shock strengthening in one embodiment of the present invention are shown below; where (a) represents the phase diagram before laser shock strengthening, (b) represents 8J-1, (c) represents 8J-2, (d) represents 8J-3, (e) represents 10J-1, (f) represents 10J-2, (g) represents 10J-3, (h) represents 12J-1, (i) represents 12J-2, and (j) represents 12J-3. Detailed Implementation

[0023] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0024] Reference Figure 1 The present invention proposes a laser shock peening method for eutectic high-entropy alloys, comprising: Establish the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy; To obtain the target laser strengthening effect of the target eutectic high-entropy alloy; Based on the target laser enhancement effect and the relationship between the target laser enhancement parameters and the target laser enhancement effect, the set values ​​of the target laser enhancement parameters are obtained; Laser shock strengthening of the target eutectic high-entropy alloy is performed based on the values ​​of the target laser strengthening parameters.

[0025] This invention pre-constructs the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy, and obtains the set value of the target laser strengthening parameters based on the target laser strengthening effect and the relationship between the target laser strengthening parameters and the target laser strengthening effect. Then, laser shock strengthening is performed on the target eutectic high-entropy alloy according to the value of the target laser strengthening parameters, realizing the synergistic improvement of the surface hardness and wear resistance of CoCrFeNiZr0.5 eutectic high-entropy alloy, and solving the problems of poor parameter adaptability and unstable strengthening effect in the prior art.

[0026] In some embodiments, the process parameters for laser shock strengthening of the target eutectic high-entropy alloy include: Laser shock energy, number of laser shocks, overlap rate, beam uniformity, and the absorption layer and constraint layer; wherein, the target eutectic high-entropy alloy is located below the absorption layer, and the absorption layer is located below the constraint layer.

[0027] In some embodiments, the target enhancement parameters include laser shock energy and the number of laser shocks.

[0028] In some embodiments, the laser shock energy is adjustable in ranges of 8 J, 10 J, and 12 J, and the number of laser shocks is adjustable in ranges of 1, 2, and 3 times, respectively.

[0029] In some embodiments, the target laser enhancement effect includes hardness and coefficient of friction.

[0030] In some embodiments, the target eutectic high-entropy alloy is a CoCrFeNiZr0.5 eutectic high-entropy alloy.

[0031] To achieve a synergistic improvement in surface hardness and wear resistance of the CoCrFeNiZr0.5 eutectic high-entropy alloy, and to address the issues of poor parameter adaptability and unstable strengthening effects in existing technologies, in some embodiments, the process of establishing the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy includes: Determine the target strengthening parameters for laser shock strengthening of the target eutectic high-entropy alloy; set the adjustment range of each target strengthening parameter; Based on the enhancement parameters of each target and their control range, an orthogonal experimental scheme was designed. Based on each experimental scheme in the orthogonal experimental scheme, laser shock strengthening was carried out on the target eutectic high-entropy alloy; Hardness and friction wear tests were performed on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various experimental schemes to obtain the target laser strengthening effect of each experimental scheme. Based on various experimental schemes and the target laser strengthening effect, the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy is established.

[0032] This embodiment establishes a laser shock energy-number matching method suitable for eutectic high-entropy alloys, achieving a synergistic improvement in the surface hardness and wear resistance of the material, with significant strengthening effect and strong controllability.

[0033] In a further embodiment, each test scheme is repeated multiple times, and the average value of the multiple target laser enhancement effects is taken as the final target laser enhancement effect.

[0034] In the execution of each experimental scheme for the target eutectic high-entropy alloy, the laser shock path is designed first; S1. Load the workpiece made of the target eutectic high-entropy alloy into the preset station; S2. Apply an absorbent layer to the impact surface of the workpiece; S3. Open the water flow switch of the constraint layer to form a water layer on the absorption layer as a constraint layer; S4. Based on the laser impact path and the process parameters in this test plan, laser impact is applied to the workpiece; S5. After each impact, determine whether the preset number of laser impacts has been reached; If yes, proceed to S6; otherwise, proceed to S2. S6. Remove the workpiece and the absorption layer to obtain the workpiece that completes the test plan.

[0035] In a further embodiment, before performing hardness and friction / wear tests on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various test schemes to obtain the target laser-strengthening effect of each test scheme, the method further includes: Optical and scanning morphology observations, phase diagrams, KAM diagrams, and XRD analyses were performed on the target eutectic high-entropy alloys before and after each experimental scheme. This facilitates the subsequent determination of the target laser strengthening effect of each experimental scheme based on the phase diagrams, KAM diagrams, optical and scanning morphology observations, XRD analysis, hardness tests, and friction and wear tests.

[0036] The present invention will now be described in conjunction with specific embodiments.

[0037] Example 1

[0038] This embodiment proposes a laser shock peening method for eutectic high-entropy alloys. The target eutectic high-entropy alloy is a CoCrFeNiZr0.5 eutectic high-entropy alloy, comprising: The relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy was established; the target strengthening parameters include laser shock energy and laser shock number, and the target laser strengthening effect includes hardness and friction coefficient. To obtain the target laser strengthening effect of the target eutectic high-entropy alloy; Based on the target laser enhancement effect and the relationship between the target laser enhancement parameters and the target laser enhancement effect, the set values ​​of the target laser enhancement parameters are obtained; Laser shock strengthening of the target eutectic high-entropy alloy is performed based on the values ​​of the target laser strengthening parameters. The laser shock strengthening process parameters for the target eutectic high-entropy alloy include: laser shock energy, number of laser shocks, an absorption layer made of 0.1 mm thick aluminum foil material, ensuring flat and bubble-free adhesion; a stable water layer of approximately 2 mm thickness as the constraint layer, with the target eutectic high-entropy alloy located below the absorption layer, and the absorption layer located below the constraint layer; a flat-topped circular laser spot with a consistent diameter; a pulse width of 15 ns; and an overlap rate of 50%. The process of establishing the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy includes: The target strengthening parameters for laser shock strengthening of the target eutectic high-entropy alloy were determined; the control range of each target strengthening parameter was set; the control range of laser shock energy was 8 J, 10 J, and 12 J, and the control range of the number of laser shocks was 1, 2, and 3 times, respectively. Based on the enhancement parameters of each target and their control range, an orthogonal experimental scheme was designed. Based on the various experimental schemes in the orthogonal experimental design, laser shock strengthening was carried out on the target eutectic high-entropy alloy. Each experimental scheme was repeated multiple times, and the average value of the multiple laser strengthening effects was taken as the final laser strengthening effect. Before and after each test, the optical morphology, scanning morphology, phase diagram and grain boundary distribution, XRD analysis, hardness test, and tribological wear test of the target eutectic high-entropy alloy were also examined to obtain the target laser strengthening effect of each test scheme; among them, the XRD analysis is as follows: Figure 2 As shown, the optical morphology is as follows Figure 3 As shown, the scan morphology is as follows Figure 4 As shown, the hardness test results are as follows: Figure 5 As shown, the friction and wear test results are as follows: Figure 6 As shown; the phase diagram and grain boundary distribution are as follows: Figure 7 and Figure 8As shown; Based on various experimental schemes and the target laser strengthening effect, the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy is established.

[0039] from Figure 2 It can be seen that the phase composition of the alloy did not change significantly after laser shock, indicating that this method achieves surface strengthening without altering the basic phase structure of the material. Meanwhile, the optical morphology (see...) Figure 3 ) and scan morphology (see Figure 4 Observations show that after being impacted with different parameters, the surface microstructure of the material is significantly refined, and the amount of bulk precipitates increases, but the eutectic structure is still maintained.

[0040] from Figure 5 It can be seen that under the low energy condition of 8 J, the hardness improvement is limited; under the condition of 10 J, the hardness reaches a peak value close to that of the third impact; under the condition of 12 J, the hardness increases with the number of impacts, but the hardness after three impacts is not significantly different from that after 10 J⁻² and 10 J⁻³ impacts. These results indicate that the optimal parameter is a window (10 J⁻² impacts), which allows the material to achieve the best strengthening effect while maintaining its structural stability.

[0041] from Figure 6 It can be seen that the friction coefficient of the alloy treated with 10 J⁻² impacts is significantly reduced, the friction curve is stable, and the wear resistance is improved. The friction performance under different energy-impact combinations exhibits a nonlinear variation law, further verifying the key influence of parameter matching on wear resistance.

[0042] This invention clarifies the influence of different parameter combinations on material properties by systematically controlling the laser shock energy (8 J, 10 J, 12 J) and the number of impacts (1, 2, 3). Experimental results show that under the condition of 10 J energy and 2 impacts, the alloy achieves the best synergistic improvement in hardness and wear resistance (see...). Figure 4 , Figure 5 This solves the problems of poor parameter adaptability and unstable enhancement effect in existing technologies.

[0043] Figure 7The phase diagrams and grain boundary distribution diagrams of the eutectic high-entropy alloy before and after LSP treatment are shown. In the original alloy, the FCC phase serves as the matrix, with a small amount of BCC phase present internally, while the HCP phase is more enriched near small-angle grain boundaries. Under low-energy / few impacts (e.g., 8J-1 alloy), dislocation substructures are formed in the grains, and small-angle grain boundaries appear in some grains, with little change in overall grain size. Under medium-energy / few impacts (e.g., 10J-2 alloy), the grains are significantly refined, with a large number of small-angle grain boundaries appearing. Under high-energy / few impacts (e.g., 12J-3 alloy), the grains are significantly refined, forming ultrafine grains, with an increase in high-angle grain boundaries, making microcracks more likely to occur. With increasing impact energy and number of impacts, the degree of grain damage intensifies, the grain size decreases, and the crystal orientation evolves towards a random distribution. This process utilizes the plastic changes induced by high-rate strain to induce a significant phase transformation in the microstructure of the impacted surface of the alloy, thereby optimizing and improving the microstructural defects generated during the alloy casting process.

[0044] Depend on Figure 8 It is known that dislocations in the original alloy are relatively concentrated, mainly clustered at the boundaries between small-angle grain boundaries and large-small grain boundaries. This is a result of the local thermal gradient and asymmetric deformation of grain boundaries caused by the extremely rapid cooling of the material. Rapid solidification and local heating and cooling cycles lead to stress accumulation and lattice distortion accumulation at grain boundaries, forming significant deformation zones in the grain boundary region. At low energies and cycles (such as the 8J-1 alloy), local high orientation aberrations mainly occur near the grain boundaries, where dislocation pile-up occurs. At medium energies and cycles (such as the 10J-2 alloy), high KAM regions appear inside some grains. At high energies and cycles (such as the 12J-3 alloy), KAM continues to increase and fills the grains. At 12J energy, the dislocation structure in the alloy reaches a saturated state.

[0045] In this embodiment, by comparing the changes in microstructure and dislocations under different impact energies and impact times, it can be found that 12J energy has a significant effect on improving the hardness and wear resistance of the alloy. After two 12J impacts, the dislocation density of the alloy increases significantly and reaches saturation after three impacts, thus exploring the ultimate modification effect of laser shock peening process on EHEA.

[0046] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A laser shock strengthening method for eutectic high-entropy alloys, characterized in that, include: Establish the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy; To obtain the target laser strengthening effect of the target eutectic high-entropy alloy; Based on the target laser enhancement effect and the relationship between the target laser enhancement parameters and the target laser enhancement effect, the set values ​​of the target laser enhancement parameters are obtained; Laser shock strengthening of the target eutectic high-entropy alloy is performed based on the values ​​of the target laser strengthening parameters.

2. The laser shock strengthening method for eutectic high-entropy alloys according to claim 1, characterized in that, The target eutectic high-entropy alloy is a CoCrFeNiZr0.5 eutectic high-entropy alloy.

3. The laser shock strengthening method for eutectic high-entropy alloys according to claim 1, characterized in that, The process parameters for laser shock strengthening of the target eutectic high-entropy alloy include: laser shock energy, number of laser shocks, overlap rate, spot uniformity, and the absorption layer and constraint layer; wherein, the target eutectic high-entropy alloy is located below the absorption layer, and the absorption layer is located below the constraint layer.

4. The laser shock strengthening method for eutectic high-entropy alloys according to claim 1, characterized in that, The target enhancement parameters include laser shock energy and the number of laser shocks.

5. The laser shock strengthening method for eutectic high-entropy alloys according to claim 1, characterized in that, The effects of laser enhancement on the target include hardness and coefficient of friction.

6. The laser shock strengthening method for eutectic high-entropy alloys according to claim 1, characterized in that, The process of establishing the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy includes: Determine the target strengthening parameters for laser shock strengthening of the target eutectic high-entropy alloy; set the adjustment range of each target strengthening parameter; Based on the enhancement parameters of each target and their control range, an orthogonal experimental scheme was designed. Based on each experimental scheme in the orthogonal experimental scheme, laser shock strengthening was carried out on the target eutectic high-entropy alloy; Hardness and friction wear tests were performed on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various experimental schemes to obtain the target laser strengthening effect of each experimental scheme. Based on various experimental schemes and the target laser strengthening effect, the relationship between the target laser strengthening parameters and the target laser strengthening effect of the target eutectic high-entropy alloy is established.

7. The laser shock strengthening method for eutectic high-entropy alloys according to claim 6, characterized in that, Before conducting hardness and friction / wear tests on the target eutectic high-entropy alloy subjected to laser-strengthened impact under various experimental schemes to obtain the target laser-strengthening effect of each experimental scheme, the following steps are also included: Optical and scanning morphology observations, phase diagrams, KAM diagrams, and XRD analyses were performed on the target eutectic high-entropy alloys before and after each experimental scheme.

8. The laser shock strengthening method for eutectic high-entropy alloys according to claim 6, characterized in that, Each test scheme was repeated multiple times, and the average value of the target laser enhancement effect from multiple tests was taken as the final target laser enhancement effect.

9. The laser shock strengthening method for eutectic high-entropy alloys according to claim 6, characterized in that, In the execution of each experimental scheme for the target eutectic high-entropy alloy, the laser shock path is designed first; S1. Load the workpiece made of the target eutectic high-entropy alloy into the preset station; S2. Apply an absorbent layer to the impact surface of the workpiece; S3. Open the water flow switch of the constraint layer to form a water layer on the absorption layer as a constraint layer; S4. Based on the laser impact path and the process parameters in this test plan, laser impact is applied to the workpiece; S5. After each impact, determine whether the preset number of laser impacts has been reached; If yes, proceed to S6; otherwise, proceed to S2. S6. Remove the workpiece and the absorption layer to obtain the workpiece that completes the test plan.